Analisis Pengaruh Fluktuasi Harga Hasil Pertanian Hortikultura Terhadap Keuntungan Penjualan Karipap Pada UMKM Mamapiet Tegal - Kharisama, Kharisma Indah Dita; Utami, Suci Nur; Juwanda, Muhammad (Journal of Agribusiness, Social and Economic, 2024)
This study aims to analyze the effect of the increase in the price of horticultural agricultural products on the profit of curry sales in Mamampiet Tegal MSMEs. This research focuses on three main horticultural commodities, namely carrots, potatoes, and chili, which are the main raw materials in making curry. The research method used is a simple linear regression analysis with independent variables in the form of horticultural raw material prices and dependent variables in the form of curry sales profits. The data used in this study is secondary data obtained from Mamampiet MSMEs and related agencies. The results of the study show that the increase in the price of carrots, potatoes, and chili has a significant influence on the decrease in curry sales profits. This increase in raw material prices has led to an increase in production costs, which is not offset by the increase in the selling price of curry. The analysis of production costs shows that total costs, revenues, profits, Net B/C ratios, and BEP (Break-Even Point) have changed significantly along with fluctuations in raw material prices. The conclusion of this study is that the increase in the price of horticultural agricultural products has a negative impact on the profit of the sale of curry pap for Mamampiet MSMEs. Therefore, it is recommended that Mamampiet MSMEs look for alternative raw materials that are more stable in price, as well as innovate products and marketing strategies to increase competitiveness and profits.